2018
DOI: 10.1177/2278533718800118
|View full text |Cite
|
Sign up to set email alerts
|

Technology Readiness and Likelihood to Use Self-Checkout Services Using Smartphone in Retail Grocery Stores: Empirical Evidences from Hyderabad, India

Abstract: Present study is an attempt to measure technology readiness of Indian customers towards self checkout service (SCS) through mobile app at retail stores at Hyderabad, India. Self-checkout services (SCS), a key offering of self service technology (SST), 'is the technological enablement of customers to make payments and complete a checkout, after shopping, with little or no interaction with a service employee.' Researchers also studied correlations between technology readiness, perceived usefulness, perceived eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 31 publications
3
21
0
1
Order By: Relevance
“…Previous studies have also linked technology readiness to users' behavioral intentions in various technology adoption contexts such as self-service technologies [86], online stock trading systems [17], and self-checkout services using smartphones [87], among others. Regarding the relationship between these two variables, the literature reports several results.…”
Section: Hypothesis 2 (H2) the Severity Of Covid-19 Positively Affect...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also linked technology readiness to users' behavioral intentions in various technology adoption contexts such as self-service technologies [86], online stock trading systems [17], and self-checkout services using smartphones [87], among others. Regarding the relationship between these two variables, the literature reports several results.…”
Section: Hypothesis 2 (H2) the Severity Of Covid-19 Positively Affect...mentioning
confidence: 99%
“…Regarding the relationship between these two variables, the literature reports several results. Some studies found a positive direct effect (e.g., [86]), others support indirect effects through other variables such as perceived usefulness and ease of use [17], and others indicated lack of significant relationship (e.g., [87]). Blut and Wang [16] in their metaanalysis about TR constructs and its impact on technology usage found an indirect effect of technology readiness on usage intention via TAM mediators (ease of use and usefulness).…”
Section: Hypothesis 2 (H2) the Severity Of Covid-19 Positively Affect...mentioning
confidence: 99%
“…The first influential publications using the referred instrument began in 2018. Mukerjee, Deshmukh, and Prasad (2018) used the TRI 2.0 to assess smartphone use in self-checkout services and concluded that Indian consumers were moderately ready to use new technologies. Wiese and Humbani (2019) applied the TRI 2.0, highlighting that mobile users are optimistic about using them but are still unsure about their purchasing experience.…”
Section: Technology Readiness (Tri)mentioning
confidence: 99%
“…They don't believe the new technology as a complex or difficult to understand [11]. They are excited about the presence of new technology and try to use it based on professional knowledge [17]. However, [24] in his study stated that users with a particular specialization that had a high level of innovativeness tend to increase network utilization.…”
Section: Introductionmentioning
confidence: 98%